The Practice and Students' Reaction toward Self and Peer-Assessment in Creative Writing Class - Susanti, Yunik (Lingual Journal of Language and Culture, 2023)
Self-assessment and peer assessment deal with promoting students' reflective effort in writing learning process. The students’ writing achievement, critical thinking, and autonomous skills are encouraged in the implementation of these teaching techniques. The purposes of this study are to implement, to know the benefits, and to find the student responses to self-assessment and peer-assessment in writing classes. This study was conducted in second-year students of English Language Department Nusantara PGRI University in Creative Writing Subject. The study used observations, student reflection notes, interviews, and documents for data collection. Data were analysed using three-step qualitative data analysis; display of data, reduction educe of data, and conclusions drawing. Data analysis showed that the benefits of peer assessment and self-assessment outweigh the drawbacks, as they can provide students with new knowledge, skills, and understanding of the writing process and student achievement. Peer assessment and self-assessment enable students to gain better experience, making it easier for them to apply and respond to their writing. The study concludes that English teachers are recommended to implement these teaching techniques in facilitating the students to fully experience their writing process and to boost the students’ writing ability. Keywords: Self-assessment, Peer-assessment, EFL, Teaching Writing, Creative Writing Class.